2022
DOI: 10.17221/231/2020-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Bacillus subtilis on the microarchitectural development of the immune system in Salmonella-challenged broiler chickens

Abstract: The effect of Bacillus subtilis on the immune responses and morphometry of the immune organs was evaluated in broilers challenged with S. gallinarum.  For this purpose, Salmonella-free birds (n = 240) were split into four groups with six replicates of ten birds each. Groups included an NC (negative control, non-infected + non-medicated), a PC-S (positive control, Salmonella-infected + non-medicated), an AT-S (Salmonella-infected + medicated with enrofloxacin), and a BS-S (Salmonella-infected + B. subtilis (2.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
1
1
0
Order By: Relevance
“…The findings of the present study are in line with the results of Sikandar et al (2021) who documented that supplementation of B. subtilis in broiler chick's production significantly improves the antibodies titer against the viral infection. The finding of the current studies is supported the by results of Mohamed et al (2022) who concluded that supplementation of B. subtilis in the broiler production significantly established the production of immunoglobulin sub-type E, A and M. Gadde et al (2017) reported that probiotics significantly improve the gut integrity by expressing the interleukin (2, 4, 10, and 11) in the poultry that leads to improvement in the immune response against the different infection in the host body.…”
Section: Discussionsupporting
confidence: 92%
“…The findings of the present study are in line with the results of Sikandar et al (2021) who documented that supplementation of B. subtilis in broiler chick's production significantly improves the antibodies titer against the viral infection. The finding of the current studies is supported the by results of Mohamed et al (2022) who concluded that supplementation of B. subtilis in the broiler production significantly established the production of immunoglobulin sub-type E, A and M. Gadde et al (2017) reported that probiotics significantly improve the gut integrity by expressing the interleukin (2, 4, 10, and 11) in the poultry that leads to improvement in the immune response against the different infection in the host body.…”
Section: Discussionsupporting
confidence: 92%
“…Injuries in the intestinal mucosa caused by bacteria of the genus Salmonella alter the intestinal physiology, reducing the absorption of nutrients and, consequently, the performance of the birds. Moreover, the competition between Salmonella and the host for nutrients, associated with the inflammatory response and the activation or dysregulation of the immune system, costs energy that may reduce FI and WG (Vandeplas et al, 2009;Quinteiro-Filho et al, 2012;Zhen et al, 2018;Sikandar et al, 2022).…”
Section: Discussionmentioning
confidence: 99%